A geographical analysis of speech-language pathology services to support multilingual children. (June 2014) - Verdon, Sarah; McLeod, Sharynne; McDonald, Simon
Abstract: The speech-language pathology workforce strives to provide equitable, quality services to multilingual people. However, the extent to which this is being achieved is unknown. Participants in this study were 2849 members of Speech Pathology Australia and 4386 children in the Birth cohort of the Longitudinal Study of Australian Children (LSAC). Statistical and geospatial analyses were undertaken to identify the linguistic diversity and geographical distribution of Australian speech-language pathology services and Australian children. One fifth of services offered by Speech Pathology Australia members (20.2%) were available in a language other than English. Services were most commonly offered in Australian Sign Language (Auslan) (4.3%), French (3.1%), Italian (2.2%), Greek (1.6%), and Cantonese (1.5%). Among 4–5-year-old children in the nationally representative LSAC, 15.3% regularly spoke and/or understood a language other than English. The most common languages spoken by the children were Arabic (1.5%), Italian (1.2%), Greek (0.9%), Spanish (0.9%), and Vietnamese (0.9%). There was a mismatch between the location of and languages in which multilingual services were offered, and the location of and languages spoken by children. These findings highlight the need for SLPs to be culturally competent in providing equitable services to all clients, regardless of the languages they speak.